2018
DOI: 10.1111/asj.13087
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐21 and microRNA‐214 play important role in reproduction regulation during porcine estrous

Abstract: Normal estrous cycle is crucial for porcine reproduction, and microRNA is closely related to regulation of estrous cycle in porcine ovaries. In this study, we found that the expression of miR-214 in porcine ovaries was higher than in many other tissues, and miR-21 expression in ovaries was significantly higher than in the uterus and pituitary. Meanwhile, miR-21 was upregulated and miR-214 was downregulated in the ovaries of high litter size (YH) pigs compared with low litter size (YL) pigs. Moreover, the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(42 reference statements)
0
9
1
Order By: Relevance
“…miR-21 plays an essential role in the cellular and physiological pathways in the reproductive system via regulating target genes. Tian et al [26] found that elevated miR-21 might maintain the porcine estrous cycle via targeting genes that are related to the mTOR, apoptosis, and steroidogenesis pathways. Donadeu et al [25] confirmed that miR-21-5p/-3p were expressed at a higher level in atretic follicles, and their target genes HIF1A, ETS1, and MSH2 were downregulated during follicle atresia.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 plays an essential role in the cellular and physiological pathways in the reproductive system via regulating target genes. Tian et al [26] found that elevated miR-21 might maintain the porcine estrous cycle via targeting genes that are related to the mTOR, apoptosis, and steroidogenesis pathways. Donadeu et al [25] confirmed that miR-21-5p/-3p were expressed at a higher level in atretic follicles, and their target genes HIF1A, ETS1, and MSH2 were downregulated during follicle atresia.…”
Section: Discussionmentioning
confidence: 99%
“…1B), which is consistent with previously published observations (22). miR-214-3p is expressed to greatest extent in porcine ovarian tissue among other body tissues (24).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing results from the ovarian tissue of Yorkshire pigs has shown that miR-214 expression significantly differs between large and small litter sizes (23). Studies have also shown that miR-214 may regulate steroids by targeting low-density lipoprotein receptor genes in rat GCs (24). We used Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) analyses to find that miR-214-3p is enriched in the TGF-beta signaling pathway and mTOR signaling pathway, and further, is involved in the physiological processes of cell proliferation and estradiol synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage stimulating 1 can regulate post-infarction cardiac injury through the JNK-Drp1-mitochondrial fission pathway [47]. Our previous research on MicroRNA-21 and microRNA-214 revealed that they play an important role in the regulation of estrous during porcine reproduction [20]. Analysis of the natural resistance-associated macrophage protein 1 encoding gene in Wannan black pig and Yorkshire identified a single nucleotide polymorphism, which was significantly associated with level of white blood cell % (p = 0.04), monocyte % (p = 0.024), rate of cyotoxin in monocyte % (p = 0.013) and CD4 -CD8 + T lymphocyte (p = 0.023) elucidating the disease-resistance of Wannan black pig compared to Yorkshire [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study about retinol-binding protein 4 (RBP4) gene and cholesteryl estertransfer protein (CETP) gene in Wannan black pig revealed that RBP4 was significantly associated with average back-fat thickness and meat color b* value, and identified a mutation in CETP, which had significant effects on the expression in liver and correlated positively with serum lipid and meat fat phenotypes [17,18]. Moreover, other genes and microRNAs related with immune traits and fertility have been identified [19,20]. However, these studies were performed only on a few genes and microRNAs.…”
Section: Introductionmentioning
confidence: 99%